Sodium salicylate sensitivity in an asthmatic patient with aspirin sensitivity. - Park, H. S. (Korean Academy of Medical Sciences, 1991)
Non-acetylated salicylates have been recommended for use as alternatives to nonsteroidal anti-inflammatory drugs (NSAIDs) in aspirin and/or tartrazine-sensitive patients. We experienced a case of an aspirin-sensitive asthmatic patient who developed a broncho-obstructive reaction after taking 100 mg of sodium salicylate. The result of this study suggests that sodium salicylate may cross-react with aspirin in aspirin-and tartrazine-sensitive patients.